Topological Characterizations for Sheaf of the Groups Formed by Topological Generalized Group - Aslan, Hatice; Efe, Hakan (My University, 2019)
In the present paper, we provide the some algebraic topological characterizations for an algebraic sheaf by meansof the topological generalized group constructed in [1] by considering both homotopy and sheaf theory.
Keywords: Matematik